Songorine modulates macrophage polarization and metabolic reprogramming to alleviate inflammation in osteoarthritis - He, Xi-Xi; Huang, Yuan-Jun; Hu, Chun-Long; Xu, Qiong-Qian; Wei, Qing-Jun (Frontiers in Immunology, 2024)
Osteoarthritis (OA) a prevalent joint disorder with multifaceted pathogenesis, macrophage dysregulation stands as a critical factor in perpetuating inflammation and joint degeneration. This study focuses on Aconitum soongaricum Stapf-derived Songorine, aiming to unravel its therapeutic mechanisms in OA. Methods involved comprehensive analyses, including PCR, Western blot, and immunofluorescence, to evaluate Songorine's impact on the joint microenvironment and macrophage polarization. RNA-seq analysis was conducted to unravel its anti-inflammatory mechanisms in macrophages. Additionally, metabolic alterations were explored through extracellular acidification rate monitoring, molecular docking simulations, and PCR assays. The study further employed oxygen consumption rate measurements to assess mitochondrial oxidative phosphorylation and evaluated Songorine's influence on macrophage oxidative stress through gene expression and ROS assays. Songorine effectively shifted macrophage polarization from a proinflammatory M1 phenotype to an anti-inflammatory M2 phenotype. Notably, Songorine induced metabolic reprogramming, inhibiting glycolysis and promoting mitochondrial oxidative phosphorylation. This metabolic shift correlated with a reduction in macrophage oxidative stress, demonstrating Songorine's potential as an oxidative stress inhibitor. In an in vivo rat model of OA, Songorine exhibited protective effects against cartilage damage and synovial inflammation, further emphasizing its therapeutic potential. This comprehensive study elucidates Songorine's multifaceted impact on macrophage modulation, metabolic reprogramming, and the inflammatory microenvironment, providing a theoretical foundation for its therapeutic potential in OA.